2022
DOI: 10.17765/2176-9168.2022v15n3e8341
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância de cultivares de soja à toxicidade do alumínio em fase inicial

Abstract: Os genótipos de soja possuem níveis distintos de tolerância aos efeitos fitotóxicos do alumínio (Al3+) e a exploração dessa característica pode ser uma importante estratégia para potencializar o uso de solos ácidos. Esta pesquisa foi realizada para investigar os efeitos do alumínio na germinação e no crescimento inicial de 25 cultivares de soja, e identificar os cultivares mais tolerantes e suscetíveis à toxicidade por Al3+. O ensaio foi realizado no laboratório de sementes da Universidade Estadual de Mato Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…There is generally little variability in the rank of importance, meaning that this score is not overly dependent on the data chosen for induction. Cabral, Maekawa, et al (2022) reported that SL and RL were the most sensitive variables for the differentiation of soybean genotypes concerning aluminium tolerance; SDM and SL were the most important features for research with soybean genotypes under drought and saline stress conditions in this study.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…There is generally little variability in the rank of importance, meaning that this score is not overly dependent on the data chosen for induction. Cabral, Maekawa, et al (2022) reported that SL and RL were the most sensitive variables for the differentiation of soybean genotypes concerning aluminium tolerance; SDM and SL were the most important features for research with soybean genotypes under drought and saline stress conditions in this study.…”
Section: Discussionmentioning
confidence: 49%
“…In tropical climate conditions, rainfall is often insufficient and fluctuates during the soybean sowing season (Patanè et al, 2013). Low soil water availability poses many challenges to Brazilian soybean producers, especially for early sowing (Cabral, Maekawa, et al, 2022). Therefore, research evaluating and identifying saline and drought‐tolerant soybean genotypes is important to maintain or improve world soybean production under stressful environmental conditions.…”
Section: Introductionmentioning
confidence: 99%